The phylosophy and applicability of ecoremediations for the protection of water ecosystems - Svirčev, Zorica; Krstić, Svetislav; Važić, Tamara (Acta geographica Slovenica, 2014)
The problem of accelerated eutrophication of the water ecosystems has not been appreciated proportionally to the development of human society today. Accelerated or fast eutrophication is detected destiny in majority of ecosystems today, mainly due to adverse human impact. This paper aims to introduce ERM methods in treating the problems arising from increased total capacity and saprobity and also accelerated eutrophication. In this way the broadness and importance of ERM as an ecosystem service for the water protection should be emphasized. The basic characteristics of ERM are its high buffer and self-protective capacities, and preservation of natural habitats and biological diversity. ERM represents the ‘returning to nature’ approach aiming to preserve or re-establish the natural balance of the ecosystems, but also a human endeavor that enables new jobs and by-side activities important for economic and social development of the human society.